Chemical composition study of coal ash content as potential material - Karmaili, Karmaili; Elma, Muthia; Wianto, Totok; Mizwar, Andy (Universitas Lambung Mangkurat, 2023)
Coal in Indonesia is used as fuel for power plants to support the availability of electricity. Besides that, several industries such as the cement, paper, textile, and fertilizer also use coal as fuel for production process. Due to that the coal waste such as ash was generating as increasing coal usage. Therefore, further research was carried out to investigate ash content and chemical composition of coal with various types of calories in the South Kalimantan and Central Kalimantan. In addition, this study provides information about management and potential processing of coal ash so that environmental pollution able to minimized. The method used to obtain primary data to determine the content of each parameter is by direct testing on each parameter for variations in the type of coal calorie. As a result, coal with low to high value has a percentage of ash content, respectively 2.5%; 2.3% and 9.7% and mineral content, respectively 77.40%; 0,96% and 95.06%. As well as the chemical composition of coal for SiO2, respectively 26.56%; 30;50% and 58.76%, Al2O3 respectively 11.14%, 12.41% and 28.86%, Fe2O3 respectively 16.12%, 16.40% and 4.24%. CaO and TiO2 respectively 0.50%, 0.64% and 1.53%. The results obtained, namely the value of ash content and the amount of minerals show an increase in each variation of the type of coal calories as well as the economic value shows a graph that always increases.